A Federal Role in Freight Planning and Finance - Rosenbloom, Sandra (RAND Corporation, 2012)
This monograph describes a federal freight policy designed to address growing challenges faced by the U.S. freight network in an environment dominated by declining revenues and public resistance to increasing taxes. The strategy emphasizes disaggregating project costs and benefits by location, stakeholder, and level of government and requiring identifiable beneficiaries to pay a share of project costs proportionate to the benefits they receive.